Cryogenic fracturing of synthetic coal specimens under true-triaxial loadings-An experimental study. (15th September 2022) - Zhao, Xinrui; Wang, Lei; Yao, Bowen; Cha, Minsu; Wu, Yu-Shu
Highlights: LN2 cryogenic fracturing can considerably enhance the permeability of synthetic coal blocks. Pre-cooling remains important even LN2 is directly used as the fracturing fluid. Water saturation has a strong impact on the fracturing performance. The water phase transition may alter the fracture orientation by introducing an expansion stress. A thermally cracked region around the borehole was observed under a microscope. Abstract: Cryogenic fracturing with liquid nitrogen (LN2 ) has been recognized as a potential and promising waterless fracturing technique for coalbed methane extraction, owing to the environmental harmlessness and low-temperature feature. Though it showed spirited performances in some field pilots in the late 20th century, it remains poorly understood, especially when LN2 is used directly as the fracturing fluid. In this work, we evaluated the performance of LN2 fracturing on cubic synthetic coal specimens under true-triaxial loadings. The study also included two subtasks that examined the necessity of a pre-cooling step and the effect of water saturation. Hence, the specimens are classified into dry and wet specimens, and the LN2 treatments are divided into two modes based on whether being pre-cooled. The results showed that the pre-cooling improved the fracturing performance of LN2 such that the breakdown pressures of the pre-cooled specimen are about 40% lower than the non-precooled ones. Based on the semilog pressure–time analysis, the pre-cooled specimens showed higher permeability enhancement (2.9- to 7.9-fold) than the non-precooled ones (1.4- to 1.7-fold). The dry specimens after LN2 fracturing gave a fracture along the direction perpendicular to the minimum horizontal stress, whereas fractures of the wet ones deviated from the expected direction. It indicates that the expansion pressure caused by the frost heaving may change the fracture orientation. In addition, small thermal cracks were observed around the borehole in the open-hole section from the cross-section of the wet specimen, which agrees with the widely accepted thermal damage theory.